Evaluating the Effect of Stop Line Visibility on Driver Compliance at Urban Intersections in Jakarta - Rian Hendris Saputra; Sutanto Soehodho; Martha Leni Siregar (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2026)
Urban intersections are critical nodes in city traffic systems, where road marking clarity is vital in guiding driver behavior and reducing violations. In rapidly growing cities such as Jakarta, the degradation of road markings, particularly stop line markings, poses a significant challenge to traffic safety and compliance. This study examines the influence of stop line marking clarity on road user compliance at urban intersections in Jakarta. The research applies a mixed-method approach that integrates field observation, speed profile analysis, Difference-in-Differences (DiD), and multiple linear regression to provide a comprehensive understanding of driver behavior. Two intersections representing different marking conditions, namely clear and faded markings, were selected as study locations. The DiD analysis shows a clear difference in violation behavior, where the intersection with clear markings has a violation rate of 22.0%, while the intersection with faded markings reaches 37.7%, resulting in a difference of 15.6%. The speed profile analysis indicates that vehicles at the intersection with faded markings maintain higher speeds at all observed distances. The largest difference occurs at 20 meters, with a speed gap of 4.74 km/h. This finding suggests that faded markings lead to delayed deceleration, while clear markings encourage earlier and more gradual speed reduction. The multiple linear regression proved that perceived marking clarity has a significant effect on violation behavior with a coefficient of 0.112 and a significance value of 0.029. The model explains 50.4% of the variation in violation behavior. Among the variables, ETLE awareness shows the strongest influence, followed by improved marking perception.